Is TV Increasing Aggression in Secondary School Students: An Enquiry? (Asian Education Studies, 2016)
Entire generation is growing with media i.e. mobile and TV etc. Television is the powerful medium of communication with a tremendous potency to inform to entertain and to educate. Its expansion has been more dramatic than that to radio or the automobile. It has become an important part of our life, so much that it is difficult to say whether it is a luxury or necessity.” India is a developing country and its selections are different in culture, ideas the way of living and thinking too. Teenagers are the backbone of the country to form a place worthy citizen. They are too tender to motivate by any act or deed. Social activists, Educationists are debating whether Television is increasing aggression of students. By taking 200 sample of secondary school students with the help of one standardized and one self-made tool, an attempt has made to explore relationship between TV viewing and aggression. Survey method was used. Investigation find there slightly difference in TV viewing of male and female students. Male students found more aggressive in comparison of their counterpart i.e. females. Television viewing has a slight effect on aggression of students but statistically it found non-significant.